Tantangan dan Keberhasilan Penerapan Model Project Based Learning (PjBL) dalam Pembelajaran Akuntansi di Sekolah Menengah Kejuruan - Jatmika, Surya; Alviantoro, Pramudya Purnomo (DIDASCO, 2025)
This study aims to evaluate the implementation of the Project-Based Learning (PjBL) model in accounting education at SMK Negeri 1 Musuk. The primary focus of the research is on planning, implementation, and student learning outcomes. The research method employed is a case study with a qualitative approach. Data collection techniques include observation, interviews, and documentation. The results reveal that lesson planning has been well-structured, including the development of project-based teaching modules relevant to students’ needs. During the implementation phase, teachers successfully integrated real-world projects into the learning process, actively involving students in discussions, data collection, and presentation of results. The PjBL model has proven effective in enhancing students’ critical thinking, creativity, and collaborative skills in accounting subjects. However, the study also identified several challenges, such as differences in students' characteristics and learning abilities, time constraints, and limited resources (facilities) to optimize PjBL implementation. The study recommends providing additional facility support and training for teachers. These findings are expected to serve as a reference for the development of innovative teaching strategies in vocational schools.